Polymer-based implantable or injectable products and methods for their preparation - Patents.com
Patent Information
- Application Number
- JP2023553360
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-03-02
- Filing Date
- 2022-03-02
- Publication Date
- 2025-03-12
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing crosslinked hyaluronic acid products face issues such as brittleness, inflammation, and poor biocompatibility due to excessive cross-linking, limiting their use in applications like intra-articular replacement therapy for osteoarthritis, where they need to be hydrophilic and lubricating.
A crosslinking method is developed that involves low-temperature crosslinking of polymers using a crosslinking agent, such as epoxy functional groups, to create a network of large crosslinked polymers with reduced modification, maintaining mechanical strength and biocompatibility.
The method produces gels with improved mechanical properties, resistance to thermal stress, and reduced degradation, suitable for long-term use as injectable or implantable products, including applications in cosmetic and therapeutic fields.
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for crosslinking polymers, such as hyaluronic acid, which allows for the production of implantable or injectable products.
[0002] The invention also relates to the implantable or injectable products thus obtained, which have remarkable properties and have several applications both in the cosmetic field (wrinkle fillers, breast augmentation, etc.), in plastic surgery (scar repair) and in the therapeutic field (viscosupplements for joints or tissue spacers, for example in urology or in the treatment of cancer by radiotherapy). [Background technology]
[0003] Products based on crosslinked polymers are now routinely used in both the cosmetic and medical fields for a variety of applications such as filling wrinkles and treating osteoarthritis.
[0004] Hyaluronic acid-based wrinkle fillers constitute a good example of the technical challenges commonly encountered with products based on cross-linked polymers.
[0005] Hyaluronic acid (HA) is a glycosaminoglycan (or GAG) found essentially in the extracellular matrix of connective tissues known as soft tissues, such as skin (as opposed to other tissues known as hard tissues, such as cartilage). In skin, hyaluronic acid is essentially synthesized by dermal fibroblasts and epidermal keratinocytes, but is physiologically degraded by hyaluronidase. With age, the amount of hyaluronic acid synthesized and its degree of polymerization decrease, contributing to the visible signs of skin aging.
[0006] Hyaluronic acid is a polymer composed of repeating disaccharide units, which occurs naturally in human connective tissue (thus qualifying it as a biopolymer) and is resorbable, i.e., can be degraded in vivo. Moreover, hyaluronic acid has the property of capturing and retaining water molecules. When hydrated, hyaluronic acid naturally forms a viscous composition that has the appearance of a gel.
[0007] These characteristics make hyaluronic acid a particularly suitable polymer for the manufacture of wrinkle-filling products, also known as "fillers", which are essentially intended to be injected. However, to improve the mechanical properties and their in vivo life span, at least a portion of the hyaluronic acid contained in these products is usually chemically crosslinked, for example with the aid of a crosslinking agent.
[0008] The cross-linking reaction has the effect of producing a network that includes molecules of hyaluronic acid linked together through molecules of cross-linking agent. The polymer network that is formed produces an aqueous gel. The more the polymer is cross-linked, the more viscous and firm the resulting gel becomes, and the more resistant it is to in vivo degradation. However, in the case of excessive cross-linking, the gel may become brittle and fragment, or may cause inflammation after implantation or injection, leading to its enzymatic degradation.
[0009] Furthermore, since this type of product is primarily intended to be injected, the gel must be sufficiently fluid to flow within the injection device and prevent clogging.
[0010] Therefore, technological solutions have been investigated to obtain products that meet these various requirements.
[0011] In fact, by varying certain parameters of the cross-linking reaction, it is possible to adjust the degree of cross-linking of the polymer, which corresponds to the ratio of the number of moles of disaccharides of the polymer that are effectively cross-linked to the total number of moles of disaccharides of the polymer.
[0012] Furthermore, in products that are in the form of aqueous gels and contain cross-linked polymers, free polymer, i.e., not cross-linked, is sometimes added, which can then be used to reduce the viscosity of the product and facilitate application by injection, which is typically accomplished with a syringe.
[0013] Especially in the context of cosmetic applications, it is beneficial to have products available that have sufficient properties of hardness and resistance to compression.Hardness is traditionally closely related to the ability of a solid or gel to resist elastic deformation stress, measured by modulus G'.Strength to resist linear compression can be used to describe the behavior of a solid or gel that is subjected to linear compressive stress, for example uniaxial stress.In general, it is considered that a material that has high strength to resist linear compression has good cohesion or cohesivity, i.e., the molecules that make up the material are connected together by a large force, which means that the material can avoid the collapse or diffusion of the product under the effect of pressure applied in a uniaxial direction.
[0014] Thus, once injected, the product is able to resist the various forces exerted upon it without bursting or diffusing from the filled zone.This type of property is typically obtained by increasing the degree of cross-linking of the hyaluronic acid present in the injectable product, with the possible drawbacks mentioned above.
[0015] Furthermore, in addition to the above mentioned bonds, the crosslinking reaction may produce chemical modifications that do not involve true crosslinking of the molecules of hyaluronic acid, but rather modify their structure. This is the case, for example, in the formation of covalent bonds between a molecule of a crosslinking agent and a single molecule of hyaluronic acid (called "grafting"). As used herein, the modification induced by the crosslinking agent is generally indicated by the term "modification", regardless of whether the modification involves true crosslinking or other modifications such as grafting. The extent of such modifications due to the crosslinking reaction can be estimated by the degree of modification ("MoD"). In general, the MoD of an injectable product containing crosslinked disaccharides corresponds to the percentage of the number of moles of crosslinking agent bound in any way to the number of moles of disaccharide units forming the polymer. On the one hand, this parameter takes into account the molecules of crosslinking agent that are actually involved in the crosslinking, i.e. those molecules of crosslinking agent that are bound between two disaccharide molecules. On the other hand, it also takes into account the molecules of crosslinking agent that are bound to a single molecule of the polymer, such as by grafting, and do not participate in the crosslinking of the polymer.
[0016] However, it has been suggested that too high a degree of modification may affect the biocompatibility of crosslinked hyaluronic acid (A. Tezel, GH Fredrickson, Journal of Cosmetic and Laser Therapy, 10(1):35-42, 2008). For example, highly modified hyaluronic acid is now suspected to be the cause of a certain number of secondary reactions (allergic, inflammatory, or even rejection reactions). This therefore constitutes an additional drawback to the fragmentation observed for highly crosslinked products. [Prior art documents] [Non-patent literature]
[0017] [Non-Patent Document 1] A. Tezel, GFredrickson, Journal of Cosmetic and Laser Therapy, 10(1):35~42, 2008 [Non-Patent Document 2] Kenne et al., Carbohydrate Polymers;91(1):410~4182, 2013 Summary of the Invention [Problem to be solved by the invention]
[0018] A further disadvantage of highly crosslinked fragmentation products is that they cannot be used as viscosupplements, e.g. in the treatment of osteoarthritis: for said application the fillers must be hydrophilic in order to swell homogeneously in the joint and be able to act properly as lubricants.
[0019] There is therefore a need for the development of injectable products that have interesting properties, especially rheological properties, but that do not suffer from the drawbacks of the highly modified hyaluronic acid gels currently available. [Means for solving the problem]
[0020] To meet all of these demands, applicants have developed a novel crosslinking method that can be incorporated into processes for preparing implantable or injectable products containing crosslinked polymers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] According to the present invention, the crosslinking of the polymer is carried out at low temperature with a crosslinking agent.
[0022] It is generally known that the crosslinking process is accelerated by high temperatures. However, surprisingly and unexpectedly, the applicant has discovered that when crosslinking is carried out at low temperatures, effective crosslinking can be achieved, leading to the production of a product that effectively has the qualities of an aqueous gel, especially from the rheological point of view. Furthermore, and unexpectedly, this method can be used to produce products with excellent mechanical properties, especially high resistance to linear compression, even at low degrees of modification. Moreover, it has been shown that the crosslinking process carried out at low temperatures prevents the degradation of the polymer chains, leading to a final product with, inter alia, a reduced amount of soluble polymer and, inter alia, excellent resistance to thermal stresses.
[0023] As a result, these gels are sufficiently resistant to the pressures used under conditions that would normally require aqueous gels of highly crosslinked polymers, without suffering from their drawbacks.
[0024] The injectable products of the invention also have good temperature stability: in fact, it has been shown that their rheological properties are relatively well preserved even after several days at high temperatures.
[0025] Finally, the injectable products prepared according to the methods described herein have the additional feature that the majority of the crosslinked hyaluronic acid contained therein is in the form of a network of large crosslinked polymers.As a result, the products of the present invention contain almost no small hyaluronic acid networks, thereby ensuring good filling or lubricating effect, being less susceptible to in vivo degradation, and ensuring good performance over a long period of time.
[0026] The present application therefore reports a method for preparing a product comprising a crosslinked polymer, the products obtained by said method, and more generally implantable or injectable products having the characteristics of such products.
[0027] The present invention then relates to a method for preparing a product based on a crosslinked polymer, comprising at least one step for crosslinking said polymer or one of its physiologically acceptable salts in the presence of a crosslinking agent, said crosslinking being carried out at low temperatures, for example in the range of about 0°C to about 10°C.
[0028] According to a first aspect, the present invention relates to a method for preparing a product containing a crosslinked polymer, the crosslinking step comprising or consisting of incubating the polymer or one of its physiologically acceptable salts in a reaction mixture with a crosslinker, advantageously having at least two epoxy functional groups, at low temperature, advantageously above 0° C. and below 10° C., more advantageously between 1° C. and 9° C.
[0029] The method of the invention is therefore carried out on polymers of interest in the context of the intended applications, particularly those routinely used in medical devices. A polymer is defined as a series of monomer units polymerized together to form a simple chain. Suitably, the polymer has free functional groups, advantageously alcohol or amine functional groups, that can react with a crosslinking agent.
[0030] According to one embodiment, the polymer used or carried out in the method of the invention is in its native form, also called "non-crosslinked polymer" or "free polymer" in the context of the present invention, i.e. a polymer that is neither crosslinked nor modified, i.e. a polymer whose chains are not crosslinked together with molecules of a crosslinker and are not grafted.
[0031] Alternatively, the method of the present invention can be carried out on a polymer that has already been partially reacted with a crosslinker.
[0032] Advantageously, the polymers implemented are biocompatible polymers, also called "biopolymers", which are naturally present in the organism into which they are intended to be injected.
[0033] According to another particular embodiment, said polymer has the advantage of being resorbable in vivo, i.e. said polymer is capable of being degraded naturally by the organism in which it is intended to be implanted or injected. This property can be tested in known manner by measuring the time required to reduce its volume, or even to disappear, in vitro or in vivo (in animal models or humans) in the presence of an enzyme capable of degrading it (for example in the case of hyaluronic acid in the presence of hyaluronidase). Competently, the product obtained in the context of the present invention has a resorption time that can be between several weeks and several months.
[0034] According to a preferred embodiment, the polymer implemented is selected from the group comprising polysaccharides, collagen and elastin.
[0035] Preferably, polysaccharides used in the context of the present invention include glycosaminoglycans (GAGs), alginates, dextran, chitosan and cellulose.
[0036] Advantageously, the polymers implemented belong to the glycosaminoglycan family (GAG). In the sense of the present invention, the term "glycosaminoglycan" denotes an unbranched polysaccharide polymer composed of a repeating disaccharide that always contains a hexosamine (glucosamine (GlcN) or galactosamine (GalN)) and another ose (glucuronic acid (GlcA), iduronic acid (IdoA), galactose (Gal)). Glucosamine is N-sulfated (GlcNS) or N-acetylated (GlcNac). Galactosamine is always N-acetylated (GalNac). Advantageously, the polymer that is a glycosaminoglycan is selected from the group that includes hyaluronic acid, chondroitin sulfate, dermatan sulfate, keratan sulfate, heparin or heparan sulfate.
[0037] A particularly suitable polymer in the context of the present invention is hyaluronic acid.In the sense of the present invention, the term "hyaluronic acid" refers to a polymer of molecules of hyalobiuronic acid, also known as β-D-glucuropyranosyl(1→3)-β-D-2-N-acetylglucosamine acid (CAS number: 499-15-0), linked together by β-1,4 glycosidic bonds.Hyalo-biuronic acid comprises one molecule of D-glucuronic acid and one molecule of D-N-acetylglucosamine linked together through alternating β-1,4 glycosidic bonds and β-1,3 glycosidic bonds.
[0038] In the sense of the present invention, a "physiologically acceptable salt" may be selected from, but is not limited to, sodium salts, potassium salts, zinc salts or silver salts. Thus, in certain embodiments, the term "physiologically acceptable hyaluronate" refers to sodium hyaluronate, potassium hyaluronate, zinc hyaluronate, silver hyaluronate and mixtures thereof, preferably sodium hyaluronate.
[0039] The method of the invention can be carried out with any molecular weight polymer, in particular with any molecular weight hyaluronic acid. Advantageously, however, in the case of hyaluronic acid, this is from 1×10 7 Advantageously, the hyaluronic acid used in the method of the invention has an average molecular weight of 5.0×10 Daltons (Da) or less. 4 Da~1×10 7 Da, advantageously 1 × 10 5 Da~5.0×10 6 It has an average molecular weight in the range of Da.
[0040] The polymers used in the context of the present invention can be easily obtained industrially using methods well known to those skilled in the art, for example hyaluronic acid can be obtained by extraction from animal tissues (e.g. rooster combs) or by bacterial fermentation.
[0041] According to a further feature, the method according to the invention uses a crosslinking agent or crosslinker capable of inducing crosslinks, i.e. bridging, between different polymer chains.
[0042] According to a particular embodiment, such compounds contain epoxy functional groups. These functional groups are capable of reacting with the polymer present, advantageously with its alcohol or amine functional groups. According to a particular embodiment, such compounds contain at least two epoxy functional groups, advantageously two epoxy functional groups ("bisepoxide"), and even more advantageously two epoxy functional groups located at each chain end, i.e. one epoxy functional group at each chain end of the compound. According to a particular embodiment, the crosslinker is selected from poly(ethylene glycol) diglycidyl ethers, also known as PEG diglycidyl ethers. The crosslinker is preferably selected from the following group: 1,4-butanediol diglycidyl ether (BDDE, CAS number: 2425-79-8), ethylene glycol diglycidyl ether (EGDE, CAS number: 2224-15-9), diethylene glycol diglycidyl ether (CAS number: 4206-61-5), and tetraethylene glycol diglycidyl ether. According to a particular embodiment, the crosslinker is 1,4-butanediol diglycidyl ether.
[0043] According to another particular embodiment, the crosslinking agent used in the method is preferably selected from PEG diglycidyl ethers in which the poly(ethylene glycol) chain does not contain more than 3 or even more than 2 oxygen atoms. The crosslinking agent is preferably selected from the group consisting of 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether and diethylene glycol diglycidyl ether, advantageously from the group consisting of 1,4-butanediol diglycidyl ether and ethylene glycol diglycidyl ether, more advantageously from the group consisting of 1,4-butanediol diglycidyl ether.
[0044] The crosslinking reaction can consist of mixing or incubating the polymer and crosslinker at a temperature ranging from about 0°C to about 10°C, or from about 1°C to about 9°C, for example.
[0045] During this reaction, the polymer is then modified by the crosslinking agent. In the context of the present invention, a "modified polymer" refers to a polymer that includes a structural modification resulting from the crosslinking process, including a crosslinking bond between two polymer molecules via a molecule of the crosslinking agent (hereinafter referred to as "crosslinking linkage"), as well as any other type of bond, such as, for example, a bond between a single molecule of the polymer and a molecule of the crosslinking agent. These latter do not participate in the crosslinking of the polymer, but constitute structural modifications. Thus, in the sense of the present invention, the structural modification resulting from the crosslinking process includes both crosslinking bonds and other types of modifications that are prone to be induced by the crosslinking reaction, such as, for example, grafting of molecules of the crosslinking agent onto the polymer. Thus, in the sense of the present invention, the concentration, or, if appropriate, the proportion, of the modified polymer corresponds to the concentration or proportion of the polymer that includes the structural modification resulting from the crosslinking process.
[0046] According to one embodiment, the polymer undergoing the crosslinking step is in solid form, for example as a fiber or powder. Advantageously, for the crosslinking reaction, the polymer is mixed with a liquid phase, possibly before or simultaneously with the crosslinking reaction. This step is easily carried out by mixing the polymer with a liquid phase, for example an aqueous solution. In the context of the present invention, the aqueous solution may be constituted by water or may comprise water and one or more other solvents, such as dimethylsulfoxide (DMSO).
[0047] Thus, the polymer or one of its physiologically acceptable salts is hydrated in an aqueous medium in a non-crosslinked form and then mixed with the crosslinker, or alternatively, the polymer or one of its physiologically acceptable salts is mixed in a non-crosslinked form with an aqueous solution of the crosslinker.
[0048] According to a particular embodiment, the crosslinking reaction is carried out in a basic medium, preferably at a pH of more than 7, or even 8, 9 or even 10 or more. The basic pH promotes the crosslinking reaction. The basic pH can be obtained by using basic solutions routinely used in the field, such as, for example, sodium hydroxide.
[0049] Thus, during the crosslinking step of the method of the present invention, the reaction mixture corresponds to a basic preparation comprising the polymer and the crosslinking agent.
[0050] The polymer concentration in the reaction mixture is adjusted by the skilled artisan. An increase in the polymer concentration can be used to accelerate the crosslinking reaction and reduce the amount of crosslinker. However, this should be compatible with good hydration of the polymer and good homogenization of the reaction medium. As for hyaluronic acid, for example, its concentration in the reaction mixture can be in the range of 50-500 mg per gram of reaction mixture, for example between 100-200 mg per gram of reaction mixture.
[0051] Moreover, the skilled person can vary, in particular, the respective amounts of crosslinker and polymer in the reaction mixture. For example, suitably, the molar ratio between the crosslinker and the disaccharide units of the polymer is about 0.5% or more. Below this ratio, the final product may be too liquid for the envisaged application. According to another embodiment, this ratio does not exceed about 10%. In one embodiment, the molar ratio is in the range of 0.5% to 10%. Above this ratio, there may be a risk that the final product obtained from the claimed method is too brittle. The term "disaccharide units of the polymer" as used in the sense of the present invention should be understood to mean the repeating disaccharide units forming the polymer as defined above. By way of example, as already mentioned, hyaluronic acid is formed from repeating units of hyalobiuronic acid, which is itself a disaccharide formed from D-glucuronic acid and DN-acetylglucosamine.
[0052] To promote a uniform reaction, the mixture may advantageously be homogenized, for example mechanically, using any method known to those skilled in the art.
[0053] Characteristically, according to the present invention, the crosslinking step is carried out at a low temperature. This temperature is advantageously above 0°C, or even above 1, 2, 3, 4 or 5°C. Preferably, this temperature is less than 10°C, or even below 9, 8, 7 or 6°C. In certain embodiments, the temperature is greater than about 0°C to less than about 10°C, for example greater than about 0°C to less than about 9°C, greater than about 0°C to less than about 8°C, greater than about 0°C to less than about 7°C, greater than about 0°C to less than about 6°C, greater than about 0°C to less than about 5°C, greater than about 1°C to less than about 10°C, greater than about 1°C to less than about 9°C, greater than about 1°C to less than about 8°C, greater than about 1°C to less than about 7°C, greater than about 1°C to less than about 6°C, greater than about 1 ...1 The temperature range is less than about 5°C, more than about 2°C to less than about 10°C, more than about 2°C to less than about 9°C, more than about 2°C to less than about 8°C, more than about 2°C to less than about 7°C, more than about 2°C to less than about 6°C, more than about 2°C to less than about 5°C, more than about 3°C to less than about 10°C, more than about 3°C to less than about 9°C, more than about 3°C to less than about 8°C, more than about 3°C to less than about 7°C, more than about 3°C to less than about 6°C, or more than about 3°C to less than about 5°C. In other embodiments, the temperature may be about 0°C, about 1°C, about 2°C, about 3°C, about 4°C, about 5°C, about 6°C, about 7°C, about 8°C, about 9°C, or about 10°C. In practice, the reaction mixture is advantageously placed in a container at the desired temperature, allowing this temperature to be maintained throughout the duration of the crosslinking reaction.
[0054] Preferably, the crosslinking step is carried out for a period of at least 24 or 48 hours, or more than 24 or 48 hours, advantageously 7, 8, 9, 10, 11, 12, 13 or even 14 days or more, possibly up to one or more weeks. Preferably, the desired temperature is maintained substantially constant throughout the duration of the crosslinking reaction.
[0055] At the end of the crosslinking reaction, the product thus obtained is advantageously in the form of a gel of modified polymer. In fact, the proper execution of the crosslinking step leads to an increase in the viscosity of the reaction mixture.
[0056] At the end of this crosslinking step, the reaction mixture may undergo a certain number of subsequent treatments, which may be carried out in the order shown or in a different order, sequentially or simultaneously.
[0057] A method according to the invention may optionally include a step for neutralization, which may lower the pH to a value below about 8, advantageously to an approximately neutral pH, typically 6.5 or more, or even 6.6, 6.7, 6.8 or 6.9 or more and 7.5 or less, or even 7.4, 7.3, 7.2, 7.1 or 7 or less. This lowering of the pH may be used to stop the crosslinking reaction, to ensure a better stability of the polymers present, or to bring the product to a pH compatible with the intended application, in particular application in body fluids or on the skin. This step may be carried out, for example, by mixing the product obtained from the crosslinking step with a composition having an acidic pH, such as, for example, a solution of hydrochloric acid (HCl). In practice, this step for neutralization may involve dilution of the mixture obtained from the crosslinking reaction.
[0058] The preparation method according to the invention may also comprise a step for dilution or hydration of the product obtained from the crosslinking reaction. This may be done, for example, by adding to the preparation a buffer solution having an appropriate pH, advantageously a neutral pH in the range of 6.5 to 7.5, for example a phosphate buffer (PBS, "phosphate buffered saline"). The dilution factor may typically vary between about 2 and 10, for example between about 4 and 8 or about 5.
[0059] It should be noted that the steps for neutralization and dilution can optionally be carried out simultaneously using appropriate solutions that can be used to obtain the desired pH and concentration, particularly of the cross-linked hyaluronic acid.
[0060] According to another aspect, the preparation method of the invention may also include a step for purification of the product obtained at the end of the crosslinking step, in particular to ensure that the crosslinking agent that has not reacted with the polymer during the crosslinking step, and possible other impurities, are removed. Advantageously, this treatment is carried out after neutralization and / or dilution. This step may be easily carried out by a person skilled in the art using any suitable known method for removing unwanted residues, such as residual crosslinking agent. This may be carried out, for example, by successive washings.
[0061] According to a particular embodiment, the method according to the invention further comprises, in addition to the crosslinking step, - a step for neutralization, preferably carried out with an acidic solution, and / or - a step for dilution, preferably carried out with a neutral solution; and / or - A step for purification, for example by washing may include.
[0062] According to one particular embodiment, the method includes all of these steps performed in this order, however, by way of example, the steps of neutralization and dilution may be simultaneous.
[0063] Furthermore, the composition of the product obtained at the end of the process according to the invention can be modified: Free (unmodified) polymer or one of its physiologically acceptable salts can be added to the product thus obtained.This step has the effect of reducing the viscosity of the product, which may prove useful in the context of injection-type preparations.Advantageously, the same polymer as that used in the crosslinking step can be added, preferably with substantially the same molecular weight.
[0064] Thus, for example, when using hyaluronic acid, a phosphate buffer containing hyaluronic acid, advantageously sodium hyaluronate, can be added. The concentration and volume of this solution can be adjusted in such a way as to obtain the desired concentration of free polymer in the final product, advantageously in the case of hyaluronic acid in the range of about 0.5 to 5 mg per gram of final product.
[0065] Taking into account the envisaged use, it may also be advantageous to add an anesthetic compound, such as, for example, lidocaine, bupivacaine, mepivacaine, etc., which has the effect of limiting the pain associated with the injection. Final concentrations of anesthetic agents ranging from about 1 to about 5 mg per gram of final product, for example, about 2 to about 4 mg per gram or about 3 mg per gram, are conventionally used. According to a preferred embodiment, the addition of an anesthetic compound, such as lidocaine, does not require any pH adjustment before its introduction into the composition.
[0066] Alternatively or additionally, other active ingredients can be added to the product obtained at the end of the method according to the invention. This can be, for example, a vasoconstrictor to reduce secondary effects associated with injection, or any active ingredient of interest in the context of the envisaged application, for example an antioxidant, in particular mannitol, or an anti-inflammatory agent. The addition of this type of active ingredient in the appropriate concentration is within the knowledge of the person skilled in the art.
[0067] By way of example, the products obtained at the end of the various steps of the process according to the invention may also be by adding a polymer in non-crosslinked form or one of its physiologically acceptable salts, and / or - by adding an anaesthetic, e.g. lidocaine, and more generally any active ingredient of interest It can be formulated.
[0068] At each of these additions, it is recommended to adjust the volume to maintain the desired concentration of polymer. These various additions can be made simultaneously or sequentially. Advantageously, the mixture can be homogenized after each addition.
[0069] Moreover, preferably, at the end of the various steps of the method of the invention, the products obtained are sterilized. Sterilization can be carried out using any of the usual suitable methods, such as, for example, sterilization by heat treatment in an autoclave. The sterilization temperature is advantageously in the range 100°C to 150°C, preferably above 121°C.
[0070] The product thus obtained is advantageously intended to be implanted in the body, preferably in the human body. A suitable method for implanting this type of product at the intended implantation site advantageously consists of injecting it into the body using an injection device such as a syringe. Thus, according to another embodiment, the product obtained using the method of the invention is packaged in one or more syringes, the volume of which is adapted to the intended use. Sterilization can be carried out before or after packaging.
[0071] The present invention also relates to an implantable or injectable product obtained by the method described herein. In one particular embodiment, the present invention relates to an implantable or injectable product obtained when the method described herein is carried out using hyaluronic acid or a salt thereof as the polymer.
[0072] Thus, according to a preferred embodiment, the present invention relates to an implantable or injectable product obtainable by the above-mentioned method, and in particular to hyaluronic acid or one of its salts, in particular sodium hyaluronate, as a particularly preferred polymer.However, the teachings of the present invention also apply to any polymer, in particular to those containing disaccharide units.
[0073] Thus, the products prepared according to the methods described herein may comprise hyaluronic acid modified with a crosslinker having at least two epoxy functional groups, preferably containing an epoxy functional group at each of its termini, more preferably selected from 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, or tetraethylene glycol diglycidyl ether.
[0074] Thus, the modified hyaluronic acid according to the invention may comprise the following different structures: - Chains of hyaluronic acid cross-linked together by a cross-linking agent; - chains of hyaluronic acid grafted with a crosslinker; - Cross-linked and grafted chains of hyaluronic acid.
[0075] When the cross-linking agent is 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, or tetraethylene glycol diglycidyl ether, the modified hyaluronic acid present in the product of the invention has chains grafted and / or cross-linked with said agent as illustrated below:
[0076] [ka]
[0077] Preferably, for the intended use, the amount of modified or crosslinked hyaluronic acid per gram of product according to the invention corresponds to about 1 to about 40 mg, advantageously about 5 to about 40 mg / g of product, more advantageously about 10 to about 25 mg / g of product.
[0078] The product is unmodified (non-crosslinked or free) hyaluronic acid, advantageously in an amount of from about 0.5 to about 5 mg / g of product, advantageously in an amount of from about 1 to about 3 mg / g of product; and / or an anaesthetic, advantageously lidocaine, preferably in an amount of about 1 mg to about 5 mg per gram of product, preferably about 3 mg per gram of product; and / or - any other suitable active ingredient, for example an antioxidant or an anti-inflammatory agent such as mannitol It may further include.
[0079] According to certain embodiments, the product does not contain any "free" crosslinker, i.e., crosslinker that is not grafted to the polymer or crosslinked.
[0080] Suitably, the product of the invention has a neutral or physiological pH, advantageously in the range of about 6 to about 8, more significantly in the range of 6.5 to 7.5. According to a particular embodiment, the pH of the product according to the invention is greater than or equal to 6.5, or even greater than or equal to 6.6, 6.7, 6.8 or 6.9, and less than or equal to 7.5, or even less than or equal to 7.4, 7.3, 7.2, 7.1 or 7, for example in the range of 6.8 to 7.2.
[0081] Characteristically, according to the invention, the product is in the form of a gel.
[0082] According to another feature, said gel is an aqueous gel, i.e. it comprises water. According to a preferred embodiment, said gel is injectable and has a viscosity that is compatible with injection systems routinely used in the field of application, in particular in syringes.
[0083] A gel is conventionally defined as a viscous composition that behaves like a solid. The physical behavior of a gel is measured and described by its elastic modulus G' and viscous modulus G''.
[0084] A suitable measure of the solid behavior of a gel is its resistance to deformation, which differs from that of a liquid. Indeed, when a deformation is applied to a solid, it often responds with a strain proportional to the imposed deformation, which can be measured using the elastic modulus G'.
[0085] The elastic modulus G' is the result of stress on deformation or strain (G' = stress / deformation) and therefore describes the energy absorbed by a solid. The higher the G', the harder the material. The elastic modulus G' is traditionally used to describe the solid component of a gel. As an example, in terms of orders of magnitude, emulsions have an elastic modulus G' on the order of Pascals, while rigid solids are generally considered to have an elastic modulus G' on the order of GigaPascals.
[0086] Thus, a "gel" as used in the context of the present invention advantageously means a composition having an elastic modulus G' of more than 10 Pa. Preferably, the products of the present invention have an elastic modulus G' ranging from about 20 to about 1000 Pa. According to a preferred embodiment, the products of the present invention exhibit an elastic modulus of more than about 20, 30, 40 or even 50 Pa. According to another preferred embodiment, the products of the present invention exhibit an elastic modulus of less than about 1000, 900, 800, 700, 600 or even 500 Pa. Advantageously, the G' value of the products of the present invention ranges from about 50 to about 500 Pa. In the context of the present invention, the G' value correlates to the degree of crosslinking of the polymers contributing to the solid content of the product envisaged.
[0087] The modulus G' of the products of the invention is determined using methods well known to those skilled in the art. In the context of the present invention, the modulus G' is preferably determined at room temperature, typically equal to 25°C, using a rheometer of Kinexus Pro type, for example, using a plate / plate geometry of 40 mm and a gap of 250 μm. Conventionally, a preshear and rest period is applied to the sample to erase the rheological memory of the sample, after which the linear viscoelastic region is determined by amplitude sweep, for example, at a fixed frequency of 1 Hz. The modulus G' can then be determined from the curve obtained in the linear viscoelastic region, where stress and displacement are linearly related.
[0088] In particular, the implantable or injectable products resulting from the method of the invention have mechanical and structural properties that distinguish them from known products. In particular, the results of the deformation resistance test provide evidence that, despite their low degree of modification, they have good cohesive properties, as indicated by their high strength to resist linear compression. The implantable or injectable products of the invention are therefore particularly characterized by these parameters.
[0089] In the context of the present invention, the strength to resist linear compression (F or uniaxial compressive strength force) is measured when compressing the product, as in the measurement of the modulus G' described above, using a rheometer of Kinexus Pro type, for example, using a 20 mm plate / plate geometry with a gap varying from 2.5 mm to 0.9 mm, at a speed of 0.1 mm / s. This measurement is advantageously carried out at room temperature, typically at a temperature equal to 25° C. Thus, in the context of the present invention, the term "strength to resist linear compression" denotes the force expressed in Newtons obtained under the test conditions described above.
[0090] Advantageously, the products of the invention have a strength against linear compression (F) of at least about 0.15 Newtons (N), advantageously at least about 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65 or 0.7 N. According to another embodiment, the strength against linear compression (F) does not exceed about 1.6, 1.55, 1.5, 1.45, 1.4, 1.35, 1.3, 1.25, 1.2, 1.15, 1.1, 1.05 or 1 N. According to a specific embodiment, the products of the invention have a strength against linear compression in the range of about 0.2 N to about 1.2 N, or even in the range of about 0.35 N to about 1 N.
[0091] The products of the present invention may also be characterized by a degree of modification or "MoD," which correlates with the modification to the hyaluronic acid induced by the crosslinker.
[0092] As stated above, the degree of modification or "MoD" indicates the biocompatibility of the product: the more modifications a product has, the less biocompatible it is, distinguishing it from the free or unmodified polymer.
[0093] The technical definition of the degree of modification, as well as the normalized method for measuring this degree of modification, are detailed in the literature Kenne et al. (Carbohydrate Polymers; 91(1):410-4182, 2013), which the skilled artisan may refer to and which is incorporated herein by reference.
[0094] In the context of the present invention, the term "degree of modification" refers to the ratio between the moles of crosslinker fixed to a polymer and the moles of disaccharide of the polymer, as determined by the method of Kenne et al. When hyaluronic acid is the polymer used, this ratio is the ratio between the moles of crosslinker fixed to hyaluronic acid and the moles of disaccharide contained in hyaluronic acid, i.e., the moles of hyalobiuronic acid as defined above. This ratio is typically expressed in the form of a percentage.
[0095] Briefly, the product is washed with a solution of sodium chloride and then filtered under vacuum using a 0.22 μm filter before digestion with chondroitinase AC overnight at 37° C. The number of moles of crosslinker fixed to the hyaluronic acid molecule and the number of moles of effectively crosslinked hyaluronic acid are determined by NMR (especially the signal corresponding to the crosslinker residue and the signal corresponding to the N-acetyl group of hyaluronic acid after correction for the number of protons carrying each signal). 1 H or if necessary 2 D) is determined using
[0096] Thus, according to the invention, the product preferably has a degree of modification (MoD) of less than about 15%, or even less than about 10%, 9%, 8%, 7%, 6%, 5.5%, 5%, 4.5%, 4%, 3.5%, 3%, 2.5%, 2%, 1.5%, 1% or 0.5%. According to a specific embodiment, the product of the invention has a degree of modification (MoD) of less than about 10%, advantageously between about 0.5% and about 6%.
[0097] It is noteworthy that for a given value of F, the products obtained have a particularly low degree of modification. The products of the invention can therefore be characterized by a value F / MoD, which corresponds to the absolute value of the ratio between the strength to resist linear compression (F), measured as above, and the degree of modification (MoD), expressed as a percentage.
[0098] Advantageously, this ratio is greater than about 0.15, greater than about 0.16, 0.17, 0.18, 0.19 or 0.2, or even greater than about 0.3, 0.4, 0.5, 0.6, 0.7 or 0.8. Moreover, this ratio may reach a value of about 0.9, or even about 1. In other words, for a degree of modification (MoD) of about 1%, the strength to resist linear compression (measured above) will be greater than about 0.2 N.
[0099] Moreover, at least in some embodiments, the inventive injectable products are particularly resistant to temperature, possibly due to the preservation of the polymer chains during the crosslinking process carried out at low temperature. In fact, as demonstrated in the experimental section, they still retain good rheological properties when exposed to a temperature of 80° C. for several days. As a result, the inventive injectable products can be characterized by this parameter, which for greater clarity is expressed as the percent preservation of the modulus G′.
[0100] In the context of the present invention, the "preservation rate of the modulus G'" corresponds to the ratio x 100 of the modulus G' (Pa) measured after storing the product at 80°C for 96 hours to the modulus G' (Pa) measured at time t0, i.e. before increasing the temperature, advantageously measured at room temperature (for example 25°C).
[0101] Preferably, the injectable products of the present invention have a modulus G' conservation of greater than about 25%, 26% or even 27%, advantageously greater than about 28%, 29%, 30%, 35%, 40%, 45%, 50% or even 60%.
[0102] In other words, the present invention relates to an implantable or injectable product, advantageously based on hyaluronic acid, whose value for the modulus G', measured after storage at 80°C for 96 hours, advantageously measured at room temperature (for example 25°C), is greater than 27% or even 28%, 29%, 30%, 35%, 40%, 45%, 50% or 60% or more of its initial value G'.
[0103] According to another embodiment, for a given initial G' value, the product of the invention will withstand higher temperatures than available products not prepared using the method of the invention, in other words, for a given value of G', the preservation rate of the product of the invention will be higher than the preservation rate of products prepared according to the prior art.
[0104] This test, known as the "forced pyrolysis" test, was used to - The physicochemical behavior of the products of the invention exposed to lower temperatures but for longer periods can be extrapolated. Accelerated ageing is performed for time / temperature equivalence. Thus, over a period of several months, it can be compared with the durability of the product in the human body at 37°C. It is possible to assess the resistance of the products according to the invention to thermal degradation which may be associated with the preparation methods, in particular with sterilization by heat treatment.
[0105] Another aspect of the present invention relates to the size of the polymer networks, especially the networks of crosslinked hyaluronic acid, present in the products obtained within the framework of the present invention.
[0106] As already mentioned, the crosslinking reaction allows the formation of a network of polymeric hyaluronic acid. The longer and / or more branched the polymer, the larger the size of the network. The size of the crosslinked polymer network thus obtained is important, especially considering the envisaged applications. In fact, below a certain size, estimated at 100 μm, it is assumed that fragments of hyaluronic acid have no filling effect. Moreover, as already mentioned, fragments of hyaluronic acid are not suitable for use as viscosupplements. Moreover, small networks of polymers (corresponding to "soluble HA") are dissolved more quickly in the organism and therefore degraded. Thus, a filling or lubricating product that contains a large amount of large polymer networks will perform better and last longer.
[0107] The evaluation of this parameter can in particular be carried out by a test consisting in carrying out an extraction of the sample (gel) with water and then passing the suspension of the gel in water through a membrane (filter, sieve) with pores having an average pore diameter of about 100 μm. Details regarding the experimental protocols that can be carried out are given in the "Examples" section below.
[0108] For example, hyaluronic acid in the form of small polymer networks (less than about 100 μm) passes through the membrane and is located in the liquid aqueous phase, as does free HA and / or lidocaine added to the product. These various amounts (extracted HA, corresponding to crosslinked HA in the form of small polymer networks, free HA and / or lidocaine) are evaluated by measuring the total amount of organic carbon (TOC) present in this phase. From this, the amount of extracted HA can then be estimated using the following formula:
[0109]
number
[0110] (In the formula, - [TOC] 合計 : Total TOC content of the extracted assay (mg / l) - 401.3: Molecular weight of HA (g / mol) - 168.2: Molecular weight of carbon in HA (g / mol) - Q 合計 : Total extraction amount (g) = sample + water - PE: sample size = gel (g) - [TOC] リドカイン TOC content of lidocaine in the extracted assay calculated using the following formula (no added lidocaine = 0):
[0111]
number
[0112] (In the formula, - 168.2: Molecular weight of carbon in lidocaine HCl (g / mol) - 270.5: Molecular weight of Lidocaine HCl (g / mol) - [Lidocaine] 抽出物 : Concentration of lidocaine HCl in the extract (mg / ml) as determined by HPLC).
[0113] From this, the percentage of hyaluronic acid in the form of a network of crosslinked polymers less than about 100 μm in size ("HA soluble") relative to the total crosslinked hyaluronic acid present in the test product can be estimated using the following formula:
[0114]
number
[0115] (In the formula, - HA extract: calculated according to the previous paragraph - [HA] 合計 : total HA content in the gel (mg / g) determined gravimetrically).
[0116] Therefore, as supported by the results of the experimental section, the products of the present invention are characterized in that the vast majority of the cross-linked hyaluronic acid they contain is in the form of polymer network with a size of more than about 100 μm.In fact, to be more clear, this characteristic is indicated by the ratio between the hyaluronic acid present in the polymer network with a size of less than about 100 μm and the total cross-linked hyaluronic acid present in the product.Those skilled in the art will have no difficulty in measuring this ratio, taking into account their general knowledge, the formula shown above for calculation, and based on the test described in the experimental section, for example.
[0117] The term "hyaluronic acid present in a polymer network of less than about 100 μm in size" as used in the context of the present invention refers only to hyaluronic acid present in the form of a polymer network, and therefore does not include free hyaluronic acid, i.e., non-crosslinked chains of hyaluronic acid added to the injectable product.
[0118] Preferably, the products of the present invention have an amount of hyaluronic acid in the form of a polymer network less than about 100 μm in size relative to the total amount of crosslinked hyaluronic acid of less than about 20%, advantageously less than about 19%, 18%, 17%, 16%, 15%, 10%, or even less than about 5%.
[0119] Thus, advantageously, the implantable or injectable products of the present invention have a percentage of crosslinked hyaluronic acid present in the form of a polymer network less than about 16%, 15%, 14%, 13%, 12%, 11%, 10% or less or even about 9%, 8%, 7%, 6% or even about 5% or less, with the percentage being in the form of a polymer network less than about 100 μm in size.
[0120] In other words, for a given value of G', the proportion of crosslinked hyaluronic acid present in the form of a polymer network with a size of less than about 100 μm will be less than that of products prepared according to the prior art.
[0121] The products according to the invention can be advantageously introduced in a sterile form into a device suitable for intradermal injection, such as a syringe. The invention therefore also relates to a kit comprising at least one product according to the invention and possibly a device suitable for intradermal injection.
[0122] According to another aspect, the invention relates to the uses of these products, in particular their cosmetic and therapeutic uses.
[0123] Thus, according to a first aspect, the present invention relates to the use of the products of the invention for the prevention and / or treatment, advantageously for filling skin defects, in particular wrinkles and fine lines or scars. These defects may concern not only the face, but also other parts of the body.
[0124] These applications are relevant both in the field of cosmetic surgery and in the field of plastic surgery.
[0125] For these applications, the products of the invention may be administered in various ways and by various routes, in particular intradermally, hypodermically, subcutaneously or into the mucous membranes of the lips.
[0126] They may be recommended for a variety of indications, which are listed here without limitation: - Volume correction; - Surface modification (scars, etc.); - Correction of fine lines on the face; - Correction of moderate to deep wrinkles; - Correction of eye contours (dark circles, folds, etc.); - Increased lip volume; - Correction of perioral wrinkles; - Breast augmentation as an alternative to prostheses; - Butt sculpture.
[0127] The characteristics of the product to be administered, particularly with regard to its strength to resist linear compression, as well as the route of administration, can be determined by the skilled artisan, particularly in light of the envisaged indication.
[0128] Furthermore, the products according to the invention have applications, for example, in the therapeutic field.
[0129] According to another aspect, the invention relates to the use of such products for the prevention and / or treatment of joint disorders, in particular osteoarthritis, in this context, the products supplement endogenous hyaluronic acid in its role as a lubricant and are called viscosupplements.
[0130] The product of the invention may have other applications that require filling of cavities or creating volumes, for example, to apply pressure or to separate tissues. Mention may be made in the field of ENT, especially for the repair of vocal cords, or in urology or ophthalmology. Another application concerns the use of this type of product to isolate organs, especially in the case of cancer treatment using radiation, for example by radiotherapy. Thus, the product of the invention may be implanted or injected between the prostate and the rectum in the case of colorectal cancer treatment. In all these applications, the product according to the invention is used as a tissue spacer.
[0131] For the purposes of the present invention, in order to provide a more concise description, it should be noted that some of the quantitative expressions presented herein are not modified with the term "about". However, it is understood that all numbers, whether or not the term "about" is explicitly used, should be understood as being modified by the term "about", whether or not it is explicitly stated. Similarly, a range presented of "about 1% to 10%" is intended to have the term "about" modify both the 1% endpoint and the 10% endpoint.
[0132] Unless expressly stated otherwise, the steps may be performed in any order, including but not limited to. EXAMPLES
[0133] The invention and advantages arising therefrom will become clearer from the following exemplary embodiments which relate to hyaluronic acid (HA) but which are not intended to limit the scope in any way.
[0134] I - PROCESS AND PRODUCTS OF THE INVENT
[0135] Example 1 Product Preparation An injectable product was prepared from the reaction mixture shown in Table 1 below:
[0136] [Table 1]
[0137] The preparation method was as follows: The average molecular weight of 1.5 MDa (1.5 × 10) required to obtain the concentrations shown in Table 1 6 A lump of sodium hyaluronate (NaHA) fiber (weight: 1.0 Da) was weighed and placed in a container.
[0138] A solution of cross-linker composed of distilled water, sodium hydroxide and 1,4-butanediol diglycidyl ether (BDDE, CAS number: 2425-79-8) in the concentrations required to obtain the ratios shown in Table 1 was added to the NaHA fibers.
[0139] The mixture was homogenized.
[0140] Once the reaction medium was mixed, the vessel was placed in a refrigerated container at a temperature ranging from 0° C. to 10° C. for several days.
[0141] At the end of this process a gel was obtained.
[0142] The gel thus obtained was hydrated to obtain the desired concentration of hyaluronic acid at physiological pH (range 6-8). The hydration bath consisted of phosphate buffer and 1N hydrochloric acid. The proportions were adapted as a function of the concentration of HA during crosslinking and the concentration to be obtained. The gel was cut into pieces and then introduced into the hydration bath.
[0143] The hydrated gel was then purified by washing with phosphate buffer to remove residual cross-linker.
[0144] Free sodium hyaluronate (i.e., not cross-linked) of average molecular weight 1.5 MDa was added to the purification gel as a function of the desired final concentration of free HA (see Table 2 below).
[0145] A 10% (w / w) solution of lidocaine was added to the injectable product to obtain a final concentration of 3 mg / g lidocaine in the gel.
[0146] The concentration of cross-linked HA was adjusted by adding phosphate buffer (see Table 2 below).
[0147] The mixture was degassed.
[0148] Once degassing was complete, the syringe was filled and then sterilized.
[0149] The resulting injectable products are listed in Table 2 below:
[0150] [Table 2]
[0151] Example 2 Mechanical and rheological properties of the resulting products The modulus G', strength resisting linear compression (F) and degree of modification (MoD) of the product prepared in Example 1 were measured.
[0152] The modulus G' was determined using a Kinexus Pro rheometer using a 40 mm plate / plate geometry with a gap of 250 μm at room temperature (25° C.). A preshear and rest period was applied to the sample to erase the rheological memory of the sample, and then the linear viscoelastic region was determined by an amplitude sweep at a fixed frequency of 1 Hz. The modulus G' was determined from the curve obtained in the linear viscoelastic region, where the stress and the displacement have a linear relationship.
[0153] The strength to resist linear compression (F) was determined using a rheometer with a 20 mm plate / plate geometry with a gap varying from 2.5 mm to 0.9 mm at a speed of 0.1 mm / s at room temperature (25° C.).
[0154] The degree of modification (MoD) was determined using the method of Kenne et al. (Carbohydrate Polymers; 91(1):410-4182, 2013). Briefly, the products to be analyzed were washed with sodium chloride solution and then filtered under vacuum using a 0.22 μm filter, followed by digestion with chondroitinase AC overnight at 37 °C. After correcting for the number of protons carrying each signal, the signals corresponding to the crosslinker residues and the signals corresponding to N-acetyl hyaluronic acid were integrated to obtain 2 The moles of crosslinker bound to a molecule of hyaluronic acid and the moles of hyaluronic acid effectively crosslinked were determined by D NMR.
[0155] The results obtained are shown in Table 3 below:
[0156] [Table 3]
[0157] Example 3 Thermal stability of the resulting products To estimate the thermal stability of the resulting pourable products, Gels A and B above were exposed to high temperatures for short periods of time.
[0158] Briefly, a sample of the product to be analyzed was placed at 80° C. for several days, for example 1, 2, 3 or 4 days. Afterwards, the sample was removed and then placed at room temperature until it cooled to room temperature. Once at room temperature, the elastic modulus G′ was measured according to the method described in Example 2.
[0159] The results obtained are shown in Table 4 below:
[0160] [Table 4]
[0161] Example 4 Estimation of the in vivo performance of the resulting products The proportion of soluble sodium hyaluronate (HA soluble) in the crosslinked fraction of the obtained HA gels was estimated after extracting the samples in water and filtering through a 100 μm sieve. Indeed, below this size, it was assumed that HA, whether crosslinked or not, has no bulking effect and is rapidly degraded in the organism.
[0162] Total organic carbon (TOC) was assayed and then HA solubility was determined by calculation.
[0163] If the resulting product contained lidocaine, the TOC provided by the lidocaine was taken into account by assaying for lidocaine present in the test sample.
[0164] Where free HA was added to the resulting product to facilitate injection rather than for loading purposes, the amount of free HA added to the product was subtracted from the HA extracted.
[0165] Extraction Protocol: Briefly, 1 gram of the product to be analyzed (sample) was mixed with 100 g of purified water. The mixture was stirred at room temperature for several hours.
[0166] Filtration Protocol: The mixture was then filtered through a cloth with pores having an average diameter of 100 μm.
[0167] Calculation of HA extracted from the product: TOC content of a-lidocaine:
[0168]
number
[0169] (In the formula, - 168.2: Molecular weight of carbon in lidocaine HCl (g / mol) - 270.5: Molecular weight of Lidocaine HCl (g / mol) - [Lidocaine] 抽出物 : Concentration of lidocaine HCl in the sample (mg / ml) as determined by HPLC).
[0170] b-Extracted HA of the resulting product (mg / g) The amount of total organic carbon (TOC) present in the resulting liquid phase (hereafter "HA extract") was measured:
[0171]
number
[0172] (In the formula, - [TOC] 合計 : Total TOC in the test sample (mg / l) - [TOC] リドカイン : TOC content in lidocaine assayed in sample (see a. above) - 401.3: Molecular weight of HA (g / mol) - 168.2: Molecular weight of carbon in HA (g / mol) - Qtotal: Total extraction volume (sample + water) - PE: sample size (g).
[0173] c. Soluble HA as a % of HA in the resulting product
[0174]
number
[0175] (In the formula, - HA extract: see b. above - [HA] 合計 : total HA content in the sample (mg / g) determined gravimetrically).
[0176] The results obtained are shown in Table 5 below:
[0177] [Table 5]
[0178] It can be seen that the amount of HA (in the form of a polymer network with a size of less than 100 μm) that is deemed soluble in the product obtained is low.As a result, in the product of the present invention, the majority of the cross-linked hyaluronic acid chains are in the form of a large polymer network, resulting in an effective filling and long-lasting performance.
[0179] II - Comparison of the product of the invention with commercial products The characteristics of the product obtained by the method of the present invention were compared with a commercial product known to be crosslinked with BDDE at high temperature (50° C.), and the data are shown in Table 6 below:
[0180] [Table 6]
[0181] III--Efficacy of the products of the invention as fillers A prospective multicenter clinical study was initiated to evaluate the safety and efficacy of the product according to the invention in the treatment of pathological facial lipoatrophy.
[0182] Both product A with a majority of B and product B as disclosed in part I of the Examples were injected into patients in two sessions (total volume of 7 ml for B and 2 ml for A) 14 days apart for the correction of facial lipoatrophy with midface augmentation. Patients were followed up for up to 12 months. Results were assessed using the Global Aesthetic Improvement Scale, GAIS.
[0183] This study made it possible to demonstrate that even after 12 months, 100% of the patients were still responders to the treatment.
Claims
1. A method for preparing a product containing a crosslinked polymer, the crosslinking step consisting of incubating said polymer or one of its physiologically acceptable salts in a reaction mixture with a crosslinker having at least two epoxy functional groups at a temperature above 0°C and below 10°C.
2. The method of claim 1 , wherein the polymer is selected from the group of glycosaminoglycans.
3. 3. The method according to claim 1 or 2, wherein the crosslinking agent is selected from 1,4-butanediol diglycidyl ether (BDDE), ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, or tetraethylene glycol diglycidyl ether.
4. 4. The method according to claim 1, wherein the crosslinking step is carried out for a period of at least 48 hours.
5. 5. The method according to claim 2, wherein the molar ratio between the crosslinker and the disaccharide units of the polymer is less than or equal to 10% and greater than or equal to 0.5%.
6. 6. The method according to claim 1, wherein at the end of the crosslinking step, the reaction mixture is subjected to at least one of the following treatments: neutralization, dilution, purification, sterilization.
7. An implantable or injectable product obtainable by the method according to any one of claims 1 to 6.
8. - Modification degree (MoD) less than 10%; and - the strength to resist linear compression (F) between 0.2N and 1.2N, or even between 0.35N and 1N, when compressed at 25°C using a rheometer with a 20mm plate / plate geometry and a gap varying from 2.5mm to 0.9mm at a speed of 0.1mm / s 8. The product of claim 7, having the formula:
9. 9. An implantable or injectable product or the product according to claim 8, having a ratio F / MoD of more than 0.
15.
10. 10. An implantable or injectable product or a product according to any one of claims 7 to 9, wherein the value for the modulus G' measured after storage at 80°C for 96 hours is more than 27%, or even 30%, 40%, 50% or 60% or more of the initial G' value.
11. 11. An implantable or injectable product or a product according to any one of claims 7 to 10, in which the proportion of cross-linked hyaluronic acid present in the form of a network with a size of less than 100 μm is less than 20%, 15%, 10% or even less than 5%.
12. 12. Product according to any one of claims 7 to 11, containing crosslinked hyaluronic acid equivalent to 1 to 40 mg / g of product.
13. A product according to any one of claims 7 to 12, containing unmodified hyaluronic acid equivalent to 0.5 to 5 mg / g (product).
14. 14. A product according to any one of claims 7 to 13, further comprising an anaesthetic agent.
15. A kit or syringe comprising a product according to any one of claims 7 to 14.
16. An agent for the prevention or treatment of skin defects comprising a product according to any one of claims 7 to 14.
17. The agent according to claim 16, for administration intradermally, hypodermically or subcutaneously.
18. An agent for the prevention or treatment of joint disorders comprising a product according to any one of claims 7 to 14.
19. A tissue spacer comprising a product according to any one of claims 7 to 14.